Observations on biotic parameters of Angora rabbit breed under controlled conditions in different housing systems - Sajid Ur Rahman; Xichun Wang; Li Yu (Veterinary World, 2018)
Aim: The aim of the present study was to compare the body weight (BW) gain and physiological parameters such as temperature, respiratory rate (RR), and heart rate (HR) of Angora rabbit reared in different housing systems.